Lessons of the financial crisis for the attractiveness of European financial centers - Gunnar Lang (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper analyses fundamental location factors for the financial industry by investigating the economic significance of market participants' assessments of location factors and country-specific characteristics over time. A unique data set allows studying the locational attractiveness of financial centers before, during, and after the recent financial crisis. The results reveal that especially dense networks in cluster concentration and governmental support strongly determine a location's attractiveness for financial institutions, whereas a specialized pool of labor alone without concentration and the level of taxation seem not to be relevant. Financial centers with a strong home market benefit during times of crisis in contrast to offshore centers and vice versa. Overall, financial centers' attractiveness varies over time, while the decisive location factors stay the same. The findings are not hinged by differences in market participants' socio-economic backgrounds. Investment fund companies seem to value the attractiveness of a financial center much more than banks, insurance companies, and corporates do.
urn:nbn:de:bsz:180-madoc-328913
Keywords: G01; G20; G28; D22; 330; Financial Crisis; Financial Center; Government Policy